Similar effects as shade tolerance induced by dust accumulation and size penetration of particulates on cotton leaves - Li Li; Guijin Mu (BMC Plant Biology, 2021)
Abstract Background Dust accumulation covers the leaf’s surface and influences foliar physiological activity. Two independent experiments were carried out to instigate the foliar responses to dust accumulation and the penetration limitation of small dust particles (< 1 μm) on the foliar surface, respectively. In experiment I, three dust accumulation intensities were achieved by a dust spraying treatment. Photosynthesis CO2 exchange and fast chlorophyll fluorescence transient were measured, as well as chlorophyll contents and leaf thickness. In experiment II, the penetration limits of small particulates on the leaf surface were examined by feeding nano-fluorescent microspheres. Results Dust accumulation alleviated the photoinhibition of Photosystem II and decreased photosynthesis, as represented by net photosynthetic rates (P N) and stomatal conductance to water vapor (g s). Photosynthetic response curves between net photosynthetic rate (P N) and photosynthetically active radiation (PAR) showed that heavy dust accumulation (34.98 ± 2.6 mg cm− 2) increased the light compensation point (LCP) and light saturation point (LSP) and decreased photosynthesis rates under saturating light (P Nmax). Leaves became thin due to the lack of a palisade layer while chlorophyll content increased under dust accumulation. Confocal laser scanning microscopy (CLSM) images showed that the larger particles (1 μm) distributed in the regions below the stomata and the smaller ones (0.1 μm) were detected in the wider areas below stomata. Conclusions These results suggested that dust accumulation induced similar effects as shade tolerance in cotton leaves but did not trigger more photochemical acclimation to low light. Dust particles (< 1 μm) penetrated leaf surface through stomata.